Direct bonding of liquid crystal polymer to glass. Issue 109 (9th November 2016) - Alam, Arif Ul; Qin, Yiheng; Howlader, Matiar M. R.; Deen, M. Jamal
Abstract : A sequential plasma-activated bonding technology is developed for the low-temperature direct bonding of liquid crystal polymer to glass. Abstract : In this paper, a direct bonding technology for liquid crystal polymer (LCP) and glass is developed for the first time by using sequential plasma-activated bonding which is based on physical sputtering followed by the formation of chemically reactive surfaces. The sequential-plasma-activated surfaces of glass and LCP show high hydrophilicity with moderate roughness. The adhesion between the activated LCP and glass surfaces is governed by hydroxyl group-mediated interfacial Si–OH–C covalent bonds. The post-bonding anodic treatment increases the amount of interfacial oxides by generating more singly-bonded oxides on the glass surface. The post-bonding thermal treatment rearranges the plasma-induced reactive sites and improves the conformal contact between the LCP and glass. A high bonding strength of 6.3 MPa is obtained between the LCP and glass when both anodic and thermal treatments are used. This simple and low-temperature direct bonding process for LCP and glass provides insights for future bonding between polymers and thin glass films.